Rhetorical Functions of Articles in SINTA Accredited Journal - Hanandyo Dardjito; Nicola Rolls; Estri Oktarena Ikrarini; Midia Puspita Sari; Anugerah Sam (Script Journal: Journal of Linguistics and English Teaching, 2023)
Background: In the past ten years or so, the publication of research journal articles has been increasing and growing. The development is even more significant when the Higher Education in Circular Letter No.152 / E / T / 2012 requires article writing for students of all levels as one of the graduation requirements. The publication of articles, especially in English-language journals, is a challenge for Indonesian authors to be able to produce scientific papers that not only meet scientific rules but also linguistic rules in English. Methodology: This study aims to see the function of rhetorical moves in English journal articles published in SINTA-accredited journals. The part of the article to be studied is focused on the Introduction which has the main role of providing general information about the research background. The rhetoric function of this article will show a series of texts that have a specific function in the Introduction. The sample of this study was taken from articles in the SINTA-accredited journals level 2 and written in English written by authors of non-English-language disciplines. Two articles were randomly selected from each journal so in total it amounted to 16 articles. Findings: This study looks at what rhetorical functions were used, and the textuality of the rhetorical functions used in the Introduction to articles written and published in SINTA-accredited journals level 2. â€œIndicating the Structure of the Research Paperâ€ and â€œAnnouncing Principal Findingsâ€ were the least two rhetorical functions stated by the authors in the Introduction section. Two articles in this study fulfil the textuality components but the rests fail to fulfill the textuality components. Conclusion: Writing journal articles in English is a great challenge for Authors with an English as a foreign language (EFL) background. Language proficiency, academic language mastery, academic writing convention and mechanics awareness which include rhetorical functions and textuality might distract their content writing competence. Originality: Many studies searched the rhetorical functions of postgraduate theses, journal articles, and thesis abstracts in English written by non-native English; however, research on journal articles by Indonesian journal publishers is limited.